Identificação e quantificação das proteínas miofibrilares, isoformas da cadeia pesada de miosina (MyHC) e o amaciamento da carne de bovinos Nelore (Bos indicus) - Malheiros, Jessica Moraes [UNESP] (2014)
This study aimed to further study the quality of beef in Nellore cattle (Bos indicus). Were used 718 animals finished in feedlot for 90 to 100 days aged 20 to 24 months of herds of four farms that are part of the breeding programs of the grupo Conexão Delta G, PAINT and Nelore Qualitas. The slaughter of animals occurred in commercial refrigerators employees, carcasses were identified and cooled for a period of 24 to 48 hours. After cooling and full establishment of rigor mortis samples of Longissimus dorsi bone (approximate thickness of 2.54 cm) between the 9th and 13th ribs, the left half carcass of each animal were harvested. Samples collected between the 12th and 13th ribs were used to evaluate the physical quality, as the rib eye area (REA), fat thickness (SFT), an index of marbling (IM), cooking loss, staining instrumental meat and shear force (SF). From the rest of the meat, aliquots for analyzes of myofibrillar fragmentation index (MFI) and total lipids (TL) were collected. After the realization of physicochemical analyzes the separation of the data was performed using a selection model of two experimental groups: (1) Group of tender meat (n = 15) and (2) Group of tough meat (n = 15) so as to obtain two contrasting groups for softness by FC. After separation of the groups (30) the identification and quantification of isoforms of myosin heavy chain (MyHC), troponin and desmin was performed by electrophoresis (SDS -PAGE) gels and photo documentation. The average value found for the REA was 72.8 cm2, as expected for Bos indicus, which showed SF and average MFI of 5.73 kg and 32.03 showing correlation of high magnitude and significant between the two parameters (rp = -0.55; p<0.01). With respect to the Index Optical Density (IOD) measured for troponin and desmin was not found different contrasting results for both groups, contrary to what was observed for MyHC, particularly for isoform ...